2016
DOI: 10.3748/wjg.v22.i15.4020
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lymph node metastasis in mixed-type early gastric cancer determined by the extent of the poorly differentiated component

Abstract: We recommend careful identification and quantitative evaluation of mixed-type early gastric cancer components after endoscopic resection to determine the intensity of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Previous reports showed the overall risk of LNM ranged from 1.4% to 5.2% for mucosal cancers, and 15% to 21.4% for submucosal cancers. [ 26 28 ] Although in our cohort, the LNM rate of early YGC rose up to 27.6% (8/29) for T1a lesions and 43.7% (7/16) for T1b lesions, which is much higher than that have been reported, the overall LNM risk in the older cohort was 13%, which is in agreement with previous studies. [ 29 ] Takatsu et al [ 5 ] reported that more YGC patients had involvement of 7 or more lymph nodes and suggested that the presence of LNM was a strong risk factor for their tumor recurrence and a strict follow-up should be adhered to for YGCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous reports showed the overall risk of LNM ranged from 1.4% to 5.2% for mucosal cancers, and 15% to 21.4% for submucosal cancers. [ 26 28 ] Although in our cohort, the LNM rate of early YGC rose up to 27.6% (8/29) for T1a lesions and 43.7% (7/16) for T1b lesions, which is much higher than that have been reported, the overall LNM risk in the older cohort was 13%, which is in agreement with previous studies. [ 29 ] Takatsu et al [ 5 ] reported that more YGC patients had involvement of 7 or more lymph nodes and suggested that the presence of LNM was a strong risk factor for their tumor recurrence and a strict follow-up should be adhered to for YGCs.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, studies [ 28 , 45 , 46 ] have focused on histological mixed-type, which was related to more aggressive biological behavior and poorer outcomes. In our study, 40% of early YGC had mixed-type, much higher than their older counterparts (40% vs 8%).…”
Section: Discussionmentioning
confidence: 99%
“…In early gastric adenocarcinomas combined with signet‐ring cell carcinoma (diffuse), the frequency of LNM is greatly increased to over 20%, as reported in single‐center cohorts from Korea, Japan, and China. This risk appears to be significantly associated with a large tumor size, more frequent submucosal infiltration and lymphovascular invasion .…”
Section: Discussionmentioning
confidence: 92%
“…In this multicenter study and previous single-center studies of Chinese patients, 8,10 the risk of LNM in early adenosquamous, neuroendocrine carcinomas, and carcinomas with lymphoid stroma, although there are few such studies, is minimal, as was also seen in Korean patients. 27 In early gastric adenocarcinomas combined with signet-ring cell carcinoma (diffuse), the frequency of LNM is greatly increased to over 20%, as reported in single-center cohorts from Korea, 28 Japan, 29,30 and China 10 . This risk appears to be significantly associated with a large tumor size, more frequent submucosal infiltration and lymphovascular invasion.…”
Section: In 2000mentioning
confidence: 96%
“…The 5-year EGC-speci c survival rate after surgical resection has been reported to be as high as 99% in patients with mucosal cancer and 96% in those with submucosal cancer [21]. However, several recent reports have indicated a difference in malignant potential between PD-EGC and MD-EGC [8][9][10][11][12][13][14][15][16]. Further, with respect to the long-term prognosis, mixed-type EGC cases with metastatic recurrence following an expanded curative endoscopic resection has been reported [22][23][24].…”
Section: Discussionmentioning
confidence: 99%